2019
DOI: 10.1007/s13762-019-02440-1
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals on sediments of a Mexican tropical lake: chemical speciation, metal uptake capacity, and chemical states

Abstract: Mobility and speciation of heavy metals in sediments of Mexican Lake Chapala were assessed through a five-step sequential extraction technique. Metal adsorption capacity of sediments was investigated from each sequential extraction through measurements of their specific surface areas using nitrogen adsorption data. X-ray photoelectron spectroscopy (XPS) was applied to every geochemical fraction to study the chemical metal species present on the surface of sediments. A low risk of detachment to water column was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Figure g–j exhibits the XPS spectra of SP-GaO x and SP-AlO x thin films. The single peak in the Ga 2p spectrum (Figure g) with binding energy located at 1117.1 eV indicated the existence of Ga 2 O 3 in the SP-GaO x thin film, while the peak in the O 1s spectrum (Figure h) of the SP-GaO x layer at 531.7 eV was also associated with Ga 2 O 3 . , In Figure i, the peak in the Al 2p spectrum observed at 72.6 eV exhibited the metallic Al in the SP-AlO x layer and the peak in the O 1s spectrum (Figure j) of the SP-AlO x thin film at 531.9 eV indicated that Al 2 O 3 existed in the SP-AlO x layer . Measurements for basic electrical switching performance were conducted on Ag/SP-GaO x /SP-AlO x /ITO and Ag/SP-AlO x /ITO RRAM devices, as illustrated in Figure .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Figure g–j exhibits the XPS spectra of SP-GaO x and SP-AlO x thin films. The single peak in the Ga 2p spectrum (Figure g) with binding energy located at 1117.1 eV indicated the existence of Ga 2 O 3 in the SP-GaO x thin film, while the peak in the O 1s spectrum (Figure h) of the SP-GaO x layer at 531.7 eV was also associated with Ga 2 O 3 . , In Figure i, the peak in the Al 2p spectrum observed at 72.6 eV exhibited the metallic Al in the SP-AlO x layer and the peak in the O 1s spectrum (Figure j) of the SP-AlO x thin film at 531.9 eV indicated that Al 2 O 3 existed in the SP-AlO x layer . Measurements for basic electrical switching performance were conducted on Ag/SP-GaO x /SP-AlO x /ITO and Ag/SP-AlO x /ITO RRAM devices, as illustrated in Figure .…”
Section: Resultsmentioning
confidence: 91%
“…48,49 In Figure 1i, the peak in the Al 2p spectrum observed at 72.6 eV exhibited the metallic Al in the SP-AlO x layer and the peak in the O 1s spectrum (Figure 1j) of the SP-AlO x thin film at 531.9 eV indicated that Al 2 O 3 existed in the SP-AlO x layer. 50 Measurements for basic electrical switching performance were conducted on Ag/SP-GaO x /SP-AlO x /ITO and Ag/SP-AlO x / ITO RRAM devices, as illustrated in Figure 2. The DC sweep process with a voltage bias applied onto TE Ag has determined current−voltage (IV) characteristics as illustrated in Figure 2a,b, and all Ag/SP-GaO x /SP-AlO x /ITO and Ag/SP-AlO x / ITO RRAM devices exhibited typical bipolar switching performance and the compliance current (CC) for the SET operation was limited at 1 mA.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the chemical speciation of heavy metals has also been widely analyzed through sequential extraction techniques to assess the potential mobility of heavy metals in aquatic systems. Some studies have shown that manganese (Mn), cobalt (Co), and Cd have strong exchangeability in sediment, suggesting their greater potential for release into the water and consequent elevated risks to aquatic organisms [23][24][25]. Therefore, the levels of heavy metals in waters are also crucial indicators for water quality evaluation, and various concentration thresholds for heavy metals have been established in water quality standards, such as the Guidelines for Drinking-Water Quality by the World Health Organization (WHO) and the Environmental Quality Standards for Surface Water by the State Environmental Protection Administration of China.…”
Section: Introductionmentioning
confidence: 99%